Physicomechanical Properties of 5-Norbornene-2,3-Dicarboxylic Acid Dimethyl Ether Polymers; Archives of Polymer Engineering and Science; Vol. 1, iss. 1 - Lyapkov A. A. Aleksey Alekseevich; Bozhenkova G. S. Galina Sergeevna; Kiselev S. A.; Smirnova N. A. Nataljya Aleksandrovna; Ashirov R. V. Roman Vitaljevich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Verpoort F. V. K. Frensis Valter Kornelius (2022, 2022)
Title screen